Impact of a Gap Junction Protein Alpha 4 Variant on Clinical Disease Phenotype in F508del Homozygous Patients With Cystic Fibrosis - Horn, Tabea; Ludwig, Michael; Eickmeier, Olaf; Neerinex, Anne H.; Maitland-van der Zee, Anke H.; Smaczny, Christina; Wagner, Thomas O. F.; Schubert, Ralf; Zielen, Stefan; Majoor, Christof; Bos, Lieuwe D.; Schmitt-Grohé, Sabina (Frontiers in Genetics, 2020)
Background: Lung disease phenotype varies widely even in the F508del (homozygous) genotype. Leukocyte-driven inflammation is important for pulmonary disease pathogenesis in cystic fibrosis (CF). Blood cytokines correlate negatively with pulmonary function in F508del homozygous patients and gap junction proteins (GJA) might be related to the influx of blood cells into the lung and influence disease course. We aimed to assess the relationship between GJA1/GJA4 genotypes and the clinical disease phenotype. Methods: One-hundred-and-sixteen homozygous F508del patients (mean age 27 years, m/f 66/50) were recruited from the CF centres of Bonn, Frankfurt, and Amsterdam. Sequence analysis was performed for GJA1 and GJA4. The clinical disease course was assessed over 3 years using pulmonary function tests, body mass index, Pseudomonas aeruginosa colonisation, diabetes mellitus, survival to end-stage lung disease, blood and sputum inflammatory markers. Results: Sequence analysis revealed one clinically relevant single nucleotide polymorphism. In this GJA4 variant (rs41266431), homozygous G variant carriers (n=84/116; 72.4%) had poorer pulmonary function (FVC% pred: mean 78/86, p<0.040) and survival to end-stage lung disease was lower (p<0.029). The frequency of P. aeruginosa colonisation was not influenced by the genotype, but in those chronically colonized, those with the G/G genotype had reduced pulmonary function (FVC% pred: mean 67/80, p<0.049). Serum interleukin-8 (median: 12.4/6.7 pg/ml, p<0.052) and sputum leukocytes (2305/437.5 pg/ml, p<0.025) were higher for the G/G genotype. Conclusions: In carriers of the A allele (27.6%) the GJA4 variant is associated with significantly better protection against end-stage lung disease and superior pulmonary function test results in F508del homozygous patients. This SNP has the potential of a modifier gene for phenotyping severity of CF lung disease, in addition to the CFTR genotype.